Incidence and outcome of subarachnoid haemorrhage in the general and emergency department populations in Queensland from 2010 to 2014. (5th February 2018) - Chu, Kevin H; Mahmoud, Ibrahim; Hou, Xiang‐Yu; Winter, Craig D; Jeffree, Rosalind L; Brown, Nathan J; Brown, Anthony FT
Abstract: Objectives: To determine: (i) incidence and outcome of subarachnoid haemorrhage (SAH) in the general population; and (ii) proportions of SAH in both the general ED population and in ED patients presenting with headache. Methods: A population‐based study in Queensland from January 2010 to December 2014 was conducted. Data were sourced from the Australian Bureau of Statistics, Queensland Hospital Admitted Patient Data Collection linked to the Queensland death registry and ED Information System. Admitted patients with SAH were identified from ICD‐10‐AM codes. Inter‐hospital transfers and repeat admissions for previously diagnosed SAH were excluded. Pre‐hospital deaths from SAH were included. ED patients with headache were identified from ICD‐10‐AM codes and finding 'headache' in the triage free‐text entry. The incidence of SAH, in‐hospital mortality, proportions of SAH in the general ED population and ED patients with headache were calculated. Results: There were 1975 incident cases of SAH in admitted patients and 294 pre‐hospital deaths from SAH. The incidence of SAH was 9.9 (95% confidence interval [CI] 9.5–10.4) per 100 000 person‐years. The incidence standardised to the 'World Standard Population' was 7.0 per 100 000 person‐years. The in‐hospital mortality was 23.8% (95% CI 22.0–25.8%). SAH was found in 1407 (1.9%, 95% CI 1.8–2.0) of ED patients with headache. Overall, there were 2.4 (95% CI 2.3–2.5) SAH per 10 000 of all ED attendances. Conclusions: The incidence of SAH was similar to that previously reported for Australia. One in 50 ED patients with headache had SAH. Ten in 50 000 ED attendances had a SAH. These estimates can assist in the risk assessment for SAH.